Eastern Caribbean Supreme Court civil procedure rules 2000 (Caribbean Law Publishing Co. KingstonJM, 2001)
Provides rules regulating the practice and procedure of the Court of Appeal and High Court in the Eastern Caribbean.
Keywords: COURTS